Modelling of salinity intrusion for transverse flow during extreme flood event in Kuala Selangor / Nuryazmeen Farhan Haron - Haron, Nuryazmeen Farhan (2018)
Estuaries are bodies of water along the coasts that are formed when fresh water from rivers flows into and mixes with salt water from the ocean. The density of seawater is greater than fresh water and it varies with salinity and temperature. Fresh water tends to float on top of the seawater because of its lower density. Human-induced activities like dredging of shipping lanes along the bottom estuarine, the dumping of industrial wastes into the water system and shoreline development influence estuarine dynamics which include mixing process. These activities lead to salinity changes and further adversely affect the estuarine ecosystem. In the first part of this study, the characteristics of the mixing between salt water (estuary) and fresh water (river), had been investigated in laboratory experiments. The experimental observation of saline fresh water mixing using Particle Imaging Velocimetry (PIV) have been carried out to analyse the Reynolds Stress, Turbulence Intensity, U for speed, V for velocity and Vorticity of salinity mixing pattern. Fresh water was released from one end of the flume channel and overflowing over weir at the other end. Meanwhile, salt water was represented by the red dye tracer released slowly through a weir and intruded horizontally to the upstream as a gravity current. The isohalines are plotted to identify the salinity patterns. The salinity levels were measured at selected stations along the channel/longitudinal (x-axis), and also in transverse (y-axis) and vertical directions (z-axis) within the time duration. The observed salinity profile showed that the bottom salinity is higher than the salinity at the water surface in a typical salt-wedge estuary characteristics. In the second part of the study, a shallow water model of salinity intrusion had been developed for a case study of the Selangor river estuary. The Shallow Water Model (SWM) had covered the river stretch from Kuala Selangor estuary up to Kg. Asahan station as the limit of saline water intrusion point. The boundary conditions included sea water level, salinity, and river discharge. The model was calibrated and validated using measured water depth and salinity data at Lembaga Kemajuan Ikan Malaysia (LKIM) Jetty, Kuala Selangor for selected events occurred in year 2000 until 2017. Later the SWM model was used to simulate the flood events at Kuala Selangor to investigate the transverse flow salinity intrusion during extreme flood event. Based on model performance using statistical analysis in terms of Root Mean Square Error (RMSE), Mean Absolute Error (MAE) and R2 values from the model calibration and validation results, it indicates that the model was able to predict the hydrodynamic and transverse flow salinity intrusion characteristics of the study area either during normal season or during extreme flood event. The analysis of salinity and water level/water depth changes due to high flood peak discharge for 50-, 100-year return periods and Probable Maximum Flood (PMF) years were presented in details. The upstream region gets a high impact on high fresh water flow due to high flood discharge as compared to the downstream where the water depth range clearly increases from the range of 4.37 to 4.59 m (50-year return period) to the range of 4.40 to 4.62 m (100-year return period), and continuously increases in the range of 4.59 to 4.83 m (PMF).